WANPRESTASI PIHAK PT. SAMBOJA INTI PERKASA PEMUAR (SIP) DALAM PERJANJIAN JUAL BELI BUAH SAWIT DI DESA PEMUAR KECAMATAN BELIMBING KABUPATEN MELAWI - VIKIRIUS VIKRAM NIM. A1012181110 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractPalm fruit is an important industrial plant producing cooking oil, industrial oil, and fuel. In Indonesia itself, a lot of oil palm plants are planted on big islands including Sumatra, Kalimantan and Sulawesi. In Kalimantan itself, in almost every district/city, there are palm fruit plantations, both owned by companies and owned by farmers. So far, many farmers have switched professions to become oil palm farmers, arguing that oil palm fruit quickly brings considerable business opportunities in agriculture or plantations, so that farmers who originally worked as ordinary farmers, have now switched professions to become oil palm farmers in particular. in Pemuar Village, Belimbing District, Melawi Regency. Obligations of PT. SIP Pemmuar pays the remaining payments to the farmers, so they can pay the remaining money for paying the palm fruit products to the Farmers. Therefore, the relationship does not always run smoothly because the agreement does not always go well, there is an act of default by the buyer (Pihak Pengusaha) due to late payment.Starting from the descriptions in the background of the study, the problem in this research is what factors cause Pihak Pengusaha Default in the Palm Fruit Sale and Purchase Agreement in Pemuar Village, Belimbing District, Melawi Regency?. The purpose of this research is to obtain data and information, causal factors, legal consequences and legal remedies regarding the implementation of the sale and purchase agreement of palm fruit between PT SIP Pemuar and oil palm farmers; In this study used qualitative research methods, with the approach of